Uji Pengaruh Pajak, Profitabilitas, dan Leverage terhadap Keputusan Transfer Pricing: (Studi Kasus Perusahaan Manufaktur) - Ni Made Kartika Putri; Artie Arditha Rachman; Lihan Rini Puspo Wijaya (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Globalization has had a significant impact on various aspects of life, including the economy, which has driven the growth of multinational companies in Indonesia. One practice that has become increasingly relevant in this context is transfer pricing, which refers to the determination of prices between divisions within a multinational company. This study aims to analyze the effects of taxes, profitability, and leverage on transfer pricing decisions in manufacturing companies, using a sample of 16 companies and data analysis with SPSS version 25. The results show that taxes and profitability do not have a significant impact, consistent with some previous studies. However, leverage was found to influence transfer pricing decisions, with companies having higher leverage tending to avoid transfer pricing practices in order to maximize profits. This study provides insights into the factors affecting transfer pricing decisions in manufacturing companies and the implications for tax management and financial strategies in the context of globalization dynamics.